“Save for a rainy day” or “live in the moment”? How does uncertainty associated with earthquakes affect people’s time preferences? - Ding, Congming; Yan, Xueying; Chen, Zhiyuan (Frontiers in Psychology, 2022)
Uncertainty caused by frequent earthquakes can permanently reshape people’s time preferences, forcing them to confront the question of whether to “save for a rainy day” or “live in the moment.” Focusing on China, this study empirically analyzes the effect of earthquake frequency on local residents’ time preferences, using seismic data from 780 BCE to 1970 CE matched to the China Family Panel Studies (2010) database (CFPS). The results show that uncertainty arising from earthquakes continuously influences residents’ time preferences and behavior. Specifically, in regions with a higher earthquake frequency, residents’ saving rate is lower and households’ consumption level is higher, suggesting that people exposed to frequent earthquakes pay more attention to the present than the future. The results further show that residents’ education investment level and average education level are lower in higher earthquake frequency regions. The empirical evidence demonstrates that differences in mindset are the primary reason for the observed regional differences in consumption, savings and education. The results of a series of robustness tests demonstrate the robustness of the above-listed findings. This research sheds new light on the relationship between natural disasters and human time preferences.